PERANAN KEBIJAKAN PUBLIK DALAM MENGATASI DEFISIT - Salasiah Salasiah (Prodi Ilmu Administrasi Negara, 2018)
The aim of this research is willing to know the solution of the regional fund (BOSDA) for the public senior high school and special department of senior high school given by the Provincial gevernment in East Kalimantan in the studying year 2017.The method of the research is libray one through the dalay newspaper Tribun Kalimantan Timur.The results of it are (1)The budget of the province has been deficit,(2)The authority of the management of the senior high school has been transfered for the local government to prvincial government based on teh regulation Number 23 /2014 on the regional government,(3)The Provincial government are not ready to fund the cost of the schools,(4.The local government break the relation with the schools concerned,(5)The schools have been suffered from the lack of the fund wehereas the parents supports has been stoped since 10 years ago based on the regulation of 12 years study’s must free study from primary schools to senior ones.The suggestions are The suggestions of it are (1)The senior high schoolsparents have to support the schools budget,(2) The authority of the management of the senior high school has to mananged by both either the local government or provincial government,(3)The Provincial government discussed with the local governments to pay the cost of the schools,(4)The local government does not break the relation with the schools concerned,(5)The education of the senior high schools has to pay school-fee.